2022
DOI: 10.3389/fonc.2022.870086
|View full text |Cite
|
Sign up to set email alerts
|

Serum Anti-BRAT1 is a Common Molecular Biomarker for Gastrointestinal Cancers and Atherosclerosis

Abstract: Atherosclerosis (AS) and cancers are major global causes of mortality and morbidity. They also share common modifiable pathogenesis risk factors. As the same strategies used to predict AS could also detect certain cancers, we sought novel serum antibody biomarkers of cancers in atherosclerotic sera sampled by liquid biopsy. Using serological antigen identification by cDNA expression cloning (SEREX) and western blot, we screened and detected the antigens BRCA1-Associated ATM Activator 1 (BRAT1) and WD Repeat Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 93 publications
(106 reference statements)
0
7
0
Order By: Relevance
“…Identification of WDR1 and CFL1 using SEREX screening. WDR1 was identified using large-scale SEREX screening with the sera of patients with a transient ischemic attack as an antigen recognized by serum IgG antibodies (13). The 172-1233 region of WDR1 cDNA (accession no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification of WDR1 and CFL1 using SEREX screening. WDR1 was identified using large-scale SEREX screening with the sera of patients with a transient ischemic attack as an antigen recognized by serum IgG antibodies (13). The 172-1233 region of WDR1 cDNA (accession no.…”
Section: Resultsmentioning
confidence: 99%
“…WD repeat-containing protein 1 (WDR1; also known as actin-interacting protein 1) regulates cofilin activity, promotes cytoskeletal remodeling, and thus facilitates cell migration and invasion (12). The presence of autoantibodies against WDR1 has been found in the sera of patients who have suffered a transient ischemic attack using SEREX screening (13). The…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the incomplete reaction was removed by silica gel chromatography (n-hexane and methanol : dichloromethane = 1 : 8), followed by spin evaporation of the product dried with anhydrous Na 2 SO 4 to give a clear, pale yellow oily compound. 1 H NMR (600 MHz, CDCl 3 ) d 7.39-7.28 (m, 4H), 6.70 (dd, J = 17.6, 10.9 Hz, 1H), 5.73 (d, J = 17.6 Hz, 1H), 5.22 (dd, J = 10.9, 2.1 Hz, 1H), 4.54 (s, 2H), 3.75-3.57 (m, 17H).…”
Section: The Synthesis Of Peovbmentioning
confidence: 99%
“…As one of the sensitive homogeneous chemiluminescence immunoassays, the luminescent oxygen channeling assay (LOCI), which combines the principles of latex agglutination and channeling, has been widely used to detect biomarkers, [1][2][3][4] kinases [5][6][7] and antigens and antibodies [8][9][10][11] since its principle was first proposed by Edwin F. Ullman et al in 1996. 12 In comparison with other sensitive homogeneous immunoassay methodology, LOCI is a homogeneous immunological detection technique using donor microspheres and acceptor microspheres as carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, low-density lipoprotein receptor-related protein-associated protein 1 (LRPAP1) played an important role in AS and digestive organ cancers, 25 and BRCA1-associated ATM activator 1 (BRAT1) was significant for gastrointestinal cancers and AS. 26 These common factors suggested that markers associated with AS might also be important in predicting the occurrence of cancer, but the discovery of common markers between them remained insufficient. Meanwhile, biomarkers found in our previous studies were based only on digestive system cancers, and studies using AS serum screening to identify pan-cancer markers were still limited.…”
Section: Introductionmentioning
confidence: 99%